The Unique Immunomodulatory Properties of MSC-Derived Exosomes in Organ Transplantation - Zheng, Qingyuan; Zhang, Shuijun; Guo, Wen-Zhi; Li, Xiao-Kang (Frontiers in Immunology, 2021)
Methods for suppressing the host immune system over the long term and improving transplantation tolerance remain a primary issue in organ transplantation. Cell therapy is an emerging therapeutic strategy for immunomodulation after transplantation. Mesenchymal stem cells (MSCs) are adult multipotent stem cells with wide differentiation potential and immunosuppressive properties, which are mostly used in regenerative medicine and immunomodulation. In addition, emerging research suggests that MSC-derived exosomes have the same therapeutic effects as MSCs in many diseases, while avoiding many of the risks associated with cell transplantation. Their unique immunomodulatory properties are particularly important in the immune system-overactive graft environment. In this paper, we review the effects of MSC-derived exosomes in the immune regulation mechanism after organ transplantation and graft-versus-host disease (GvHD) from various perspectives, including immunosuppression, influencing factors, anti-inflammatory properties, mediation of tissue repair and regeneration, and the induction of immune tolerance. At present, the great potential of MSC-derived exosomes in immunotherapy has attracted a great deal of attention. Furthermore, we discuss the latest insights on MSC-derived exosomes in organ transplantation and GvHD, especially its commercial production concepts, which aim to provide new strategies for improving the prognosis of organ transplantation patients.